Encircle the Pole Star and Encompass Taiyi: On the Astronomical Vision of Politics in the Laozi - Li, Zhikun (Religions, 2024)
The sentence from the tenth chapter of the Laozi, wherein the character “zai” is the last character of the preceding chapter, “po” denotes the ancient polar star Kaiyang, and “yi” signifies the celestial pole Taiyi, finds its roots in ancient Chinese astronomy. “yingpo” conveys the meaning of “encircling the polar star”, whereas “baoyi” signifies “encompassing Taiyi”, thereby metaphorically representing a framework of harmonious order. The depiction of the universe by the author of the Laozi, rooted in ancient astronomical understanding, serves as a political guide for rulers. It suggests that rulers should value the movement pattern of Taiyi, refrain from intervention, and prioritize the inherent qualities of their subjects, thus facilitating their natural development. The entire tenth chapter is centered around this central thesis.